Interferometric Synthetic Aperture Radar (InSAR) and its Potential to Monitor Subsidence Over Caving Zones Induced by Underground Mining - H Zahiri (The Australasian Institute of Mining and Metallurgy, 2008)
Utilisation of the InSAR technique for monitoring of subsidence in mining areas, employing open pit and underground mining methods, has large potential due to sensitivity and safety issues associated with usage of the classical surveying techniques. InSAR can also be very competitive concerning the cost of provided results. However, there are a few issues that may significantly limit InSAR applicability for subsidence monitoring in mining areas. The altered terrain topography, involving steep slopes and deep pits, may lead to the layover of radar signal for specific satellite and pit geometry. Also, the highly dynamic character of subsidence induced by mining, especially using mass mining methods, may lead to issues such as apparent heave and ambiguous results. In this paper the authors analyse the above-mentioned issues and demonstrate how InSAR technology was applied, as a supporting system, to monitor large scale and highly dynamic subsidence for a real case study in Western Australia.